2007
DOI: 10.1089/scd.2006.0100
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin, Vitronectin, and Collagen I Induce Chemotaxis and Haptotaxis of Human and Rabbit Mesenchymal Stem Cells in a Standardized Transmembrane Assay

Abstract: The mesenchymal stem cell (MSC) is a critical element in tissue repair and regeneration. Its ability to differentiate into multiple connective tissue cell types and to self-renew has made it a prime candidate in regenerative medicine strategies. Currently, the environmental cues responsible for in situ recruitment and control of MSC distribution at repair sites are not entirely revealed and in particular the role of extracellular matrix (ECM) proteins as motogenic factors has not been studied. Here we have use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 88 publications
(123 reference statements)
5
58
0
1
Order By: Relevance
“…Color images available online at www.liebertpub.com/tea noncollagenous proteins, including fibronectin, fibromodulin, biglycan, and decorin, all of which are known to regulate MSC activities, such as adhesion, proliferation, stemness, and differentiation. 21,[43][44][45] In addition, a variety of growth factors, such as TGF-b, IGF-1, vascular endothelial growth factor (VEGF), and connective tissue growth factor (CTGF), were found embedded in the decellularized tECM. 46 How these bioactive molecules, along with other yet-to-be-identified components in the tECM, contribute to the bioactivity of the tECM in our results remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Color images available online at www.liebertpub.com/tea noncollagenous proteins, including fibronectin, fibromodulin, biglycan, and decorin, all of which are known to regulate MSC activities, such as adhesion, proliferation, stemness, and differentiation. 21,[43][44][45] In addition, a variety of growth factors, such as TGF-b, IGF-1, vascular endothelial growth factor (VEGF), and connective tissue growth factor (CTGF), were found embedded in the decellularized tECM. 46 How these bioactive molecules, along with other yet-to-be-identified components in the tECM, contribute to the bioactivity of the tECM in our results remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The functional role of ECM gradients still remains to be elucidated, though their role in guiding the migration of mesenchymal stem cells appears to be crucial during tissue repair or regeneration. For example, fibronectin, collagen I and vitronectin, presented in both soluble and bound gradient, are able to induce cell motility (Thibault et al, 2007). Also proteoglycans play a role in the spatial and temporal control of cell movement imposing directionality and stop-go choice of migrating cells (Cattaruzza and Perris, 2005).…”
Section: Defined Gradients Of Ecm Peptides Direct Cell Polarization Amentioning
confidence: 99%
“…Furthermore, chemotaxis and homing of MSCs are closely associated with ECM components. A previous study demonstrated that three ECM proteins, fibronectin (FN), vitronectin and collagen I (Col-I), induce significant mitogenic activity in MSCs (17). The ECM also stimulates neuronal differentiation of MSCs and serves as a nerve-regenerative scaffold (18,19).…”
Section: Introductionmentioning
confidence: 99%